2018
DOI: 10.1080/09638288.2018.1457092
|View full text |Cite
|
Sign up to set email alerts
|

Participation of children and youth with neurodevelopmental disorders in after-school activities

Abstract: Participants with disability participate in social, leisure and recreational activities less than their typically developing peers. The activities in which they participate are mainly stereotypical, highly structured, and take place in the presence of parents. IMPLICATIONS FOR REHABILITATION Forming a richer network of support services which would be oriented towards organizing social, leisure and recreational activities of persons with disabilities in the community. It is necessary to improve support programs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…Therefore, the results of this research are interpreted by engaging support services for socially vulnerable groups which partly neutralize the negative influence of poverty of ID persons' parents (Kaljača, Cvijetić & Dučić, 2014). More recent studies determined that regardless of engaging support services, persons with ID participated in mentioned leisure activities significantly less than TD persons (Kaljača, Dučić & Cvijetić, 2018). Transportation costs were given as one of the possible causes of limited participation of persons with ID in activities such as: socializing with friends, going to a store or church (Abbott & McConkey, 2006).…”
Section: Correlationsmentioning
confidence: 75%
“…Therefore, the results of this research are interpreted by engaging support services for socially vulnerable groups which partly neutralize the negative influence of poverty of ID persons' parents (Kaljača, Cvijetić & Dučić, 2014). More recent studies determined that regardless of engaging support services, persons with ID participated in mentioned leisure activities significantly less than TD persons (Kaljača, Dučić & Cvijetić, 2018). Transportation costs were given as one of the possible causes of limited participation of persons with ID in activities such as: socializing with friends, going to a store or church (Abbott & McConkey, 2006).…”
Section: Correlationsmentioning
confidence: 75%
“…Both groups of children showed the highest levels of independence during outside play, since independence in this domain is expressed to the greatest extent through the child’s ability to move, climb, and run independently, which was not a dominant problem for the children included in this research, similar to previous research [ 42 ]. Children’s participation in various activities is influenced by the type of disability, and children with intellectual disability show less dependence on parental support compared to children with ASD and greater independence in social and leisure activities [ 43 ]. Young children with CP participate less often in family and recreational activities and require more help to participate in self-care than young children without CP [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…This outcome is consistent with previous research. While exploring the level of participation in several leisure and social activities, Kaljača et al found that children with neurodevelopmental disabilities not only participated significantly less than TD children, but also that their activities were mainly stereotypical and highly structured, and were mostly supervised by parents [ 61 ]. Social cognition has been reported to be limited in these children as well, and it is associated with motor parameters, which further restricts daily participation [ 20 , 24 , 62 ].…”
Section: Discussionmentioning
confidence: 99%